Crashing heat - Castle, Richard (Kingswell, 2019)
New York Police Captain Nikki Heat is accustomed to dealing with murders, even those with no leads and no motives. But having her husband as a suspect makes her newest case the most personal one yet. Nikki Heat does not like to be away from her husband, Pulitzer Prize winning journalist Jameson Rook. But when Rook is given the honor to be a visiting professor at his alma mater, he can't pass up the opportunity to mentor bourgeoning journalists at his former award-winning college newspaper. Then one of Jameson's students is discovered, naked, in his bed. Now all eyes are on Jameson. Dealing with betrayal from any man is not Nikki's style. Against her better judgment, Nikki gives Jameson the benefit of the doubt and digs into Jameson's theory of an undergrad secret society.